AB0489 Correlation between vestibular function and raynaud's phenomenon. (23rd January 2014) - Bruno, C.; Petrolo, C.; Grembiale, A.; Naty, S.; Chiarella, G.; Grembiale, R. D.
Abstract : Background: Raynaud's phenomenon (RP) is caused by short term constriction of the small arteries in the extremities, usually the fingers. Primary Raynaud phenomenon is a benign condition caused by functional changes in blood vessels and/or their innervation, and by definition does not progress to irre-versible tissue injury. By contrast, patients with Raynaud phenomenon secondary to an underlying disease can have digital ulcera-tion, scarring, or gangrene. Many conditions, such as sys-temic sclerosis (SSc), systemic lupus erythematosus (SLE), vasculitis, atherosclerosis and hypothyroidism, can result in secondary Raynaud phenomenon (1 ). Primary RP is often associated with migraine, retinopathy and Prinzmetal's angina. That suggests the hypothesis that RP is a systemic disorder with spasms not only of the peripheral arteries, but also with spasms of the coronary vessels, the arterioles of the lung, the brain, the retina and the gastrointestinal tract with potential tissue injury (2 ). No previous study evaluated the possible impairment of the vestibular system from primary and secondary Raynaud's phenomenon Methods: We studied 16 patients, 15 women and 1 man, 11 with primary RP and 5 affected by secondary RP associated with SSc. All patients underwent to naifold videocapillaroscopy, equipped with 200x contact lenses, and inner ear evaluation that consists in complete vestibular examination with kinetic and caloric test by VNG method, Vestibular Evoked Myogenic Potentials (VEMPS), Ocular Vestibular Evoked Myogenic Potentials (OVEMPS), tonal and impedance audiometry. Results: We found 5 patients with RP had normal capillaroscopy while 6 patients with RP had capillaroscopy abnormalities (<20% capillary tortuosity). Caloric vestibular test was abnormal both in patients with primary RP without and in those with capillaroscopy abnormalities. VEMPS and OVEMPS was abnormal both in patients with primary RP without and in those with capillaroscopy abnormalities. SSc patients had abnormal caloric vestibular test, VEMPS and OVEMPS. (Tab.1) 12 patients had normal hearing test, 3 patients showed a bilateral perception deficit for the high frequencies, and 1 patient had a transmission deficit. Conclusions: Primary Raynaud phenomenon seems to be a benign condition but our data showed that patients with it has abnormal vestibular tests. Both patients with primary RP and capillaroscopy alterations as patients with RP but without alterations capillaroscopy showed vestibular abnormalities similar to patients with SSc. These results suggest that transitional vascular alterations, typical of the RP, can determine early injury in very sensitive tissue to hypoxic stimulus as vestibular system. Abnormalities of vestibular function may be an early sign of hypoxic damage due to this phenomenon. Further studies, with a larger sample, are needed to confirm this findings. References: Herrick, A. L. Nat. Rev. Rheumatol. 8, 469–479 (2012); Lambova S.N.· Müller-Ladner U. Rheumatol Int (2009) 29:1263–1271 Disclosure of Interest: None Declared